Definition of Internal Mammary Node Target Volume Based on the Position of the Internal Mammary Sentinel Lymph Nodes Presented on SPECT/CT Fusion Images - Wang, Xue; Wang, Wei; Li, Jian-Bin; Huo, Zong-Wei; Xu, Min; Qiu, Peng-Fei; Zhang, Ying-Jie; Li, Feng-Xiang; Wang, Jin-Zhi (Frontiers in Oncology, 2020)
Purpose: Postoperative irradiation of internal mammary node (IMN) is commonly recommended for breast cancer patients with high recurrence risk. Determining the precise IMN clinical target volume (CTV) is crucial. We mapped the distribution of internal mammary sentinel lymph nodes (IM-SLNs) presented on single photon emission computed tomography (SPECT) in conjunction with computed tomography (SPECT/CT) images to investigate the coverage of IMN CTVs defined by the Radiation Therapy Oncology Group (RTOG) and Danish Breast Cancer Cooperative Group (DBCG) guidelines. Materials and methods: Breast cancer patients who underwent preoperative lymphoscintigraphy by SPECT/CT and had imaging of IM-SLN were selected. The imaging IM-SLNs on SPECT/CT of every eligible patients were projected onto corresponding anatomical positions of a representative axial CT images. The IMN CTVs were delineated on the representative axial CT images according to the RTOG and DBCG guidelines, and defined as CTVRTOG and CTVDBCG. The intercostal space location of IM-SLNs were recorded. The positional relationship between the central point of IM-SLNs and entire volume of IM-SLNs and the two CTVs were determined, respectively. Results: Ninety-seven patients with 136 IM-SLNs were eligible. The number of IM-SLNs at the first to fifth intercostal spaces were 55(40.4%), 41(30.2%), 33(24.3%), 6(4.4%), and 1(0.7%), respectively. The average distance between the edge of CTVRTOG to the centre points of the IM-SLNs and the edge of the IM-SLN5mms was 4.10 mm and 6.40 mm, respectively. For the CTVDBCG, the average distance to the centre points of the IM-SLNs and the edge of the IM-SLN5mms was 1.60 mm and 3.34 mm, respectively. The coverage rates of IM-SLN central points by CTVRTOG and CTVDBCG were 18.4% and 60.3%. For 90% coverage of IM-SLN central points, CTVRTOG needed to be expanded by 8 mm, and CTVDBCG needed to be expanded by 5 mm. Conclusion: Neither the RTOG nor DBCG consensus guideline about the delineation of IMN CTV was sufficient to cover 90% of IM-SLNs. In order to achieve more comprehensive coverage of the IMN while patients undergo prophylactic IMNI, the location of IM-SLNs should be taken into account when evaluating and updating the guideline for delineation of IMN CTV.